Formalizing a Debt Management Strategy - Magnusson, Tomas I. (World Bank, Washington, DC, 2013)
In short, central government debt management can be defined as the process of establishing and executing a strategy in order to meet the debt management objectives. Undoubtedly, the development of the strategy is the most important debt management decision. Given the market constraints, it is the strategy document that decides on issues such as the level of exposure to foreign currency risk, desired maturity structure of the debt, level of interest rate sensitivity, whether and how much of the debt should be indexed to inflation, and the plan for development of the domestic debt markets. If the government has chosen a strategy that turns out to be too risky, or, at the other end of the spectrum, too costly in order to avoid any risk, it will affect the budget outcome much harder than any misprized and/or badly timed debt management transaction. This paper will discuss the appropriate organizational arrangement, internal procedures and regulatory framework for a successful and sustainable development of debt management strategies.